Preventing Sexual Abuse: Perspectives of Minor-Attracted Persons About Seeking Help. (December 2019) - Levenson, Jill S.; Grady, Melissa D.
The primary aim of this exploratory research was to gain information from minor-attracted persons (MAPs) about their (a) formal and informal experiences with help-seeking for minor attraction, (b) perceived barriers to seeking help for concerns about minor attraction, and (c) treatment priorities as identified by consumers of these services. A nonrandom, purposive sample of MAPs ( n = 293, 154 completed all questions) was recruited via an online survey. Results show that 75% of participants did seek formal help from a professional; however, just less than half of them found the experience to be helpful. Characteristics of helpful therapeutic encounters included nonjudgmental attitudes, knowledge about minor attraction, and viewing clients in a person-centered and holistic way. Barriers to help seeking included uncertainty about confidentiality, fear of negative reaction or judgment, difficulties finding a therapist knowledgeable about MAPs, and financial constraints. Understanding or reducing attraction to minors were common treatment goals, but participants also prioritized addressing general mental health and well-being related to depression, anxiety, loneliness, and low self-esteem. Implications for effective and ethical counseling and preventive interventions for MAPs are discussed.